Peer Support, Emotional Intelligence, Career Decision Self-Efficacy And Career Adaptability Among Certified Internship Students In The Merdeka Campus Program - Abdul Haeba Ramli; Cendy Fauziah Trianingrum; Kusnadi Kusnadi; James Ronald O. Mesina (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Students with good career adaptability can effectively plan their careers and take responsibility for their career decisions. Through the Merdeka Campus Certified Internship Program, students can develop career adaptability, preparing them to face challenges and changes in the workforce. This study aims to examine the direct influence of peer support, emotional intelligence, and career decision self-efficacy on career adaptability. The research employs a quantitative approach, targeting students from Esa Unggul University Jakarta who have participated in the Merdeka Campus Certified Internship Program. Data was collected using a questionnaire with a sample size of 130 respondents and analyzed using Structural Equation Modeling (SEM PLS) with statistical software. The results show that peer support positively influences career decision self-efficacy. Furthermore, a positive influence of emotional intelligence on career decision self-efficacy was found. Additionally, career decision self-efficacy positively affects career adaptability. However, while emotional intelligence positively influences career decision self-efficacy, it does not directly impact career adaptability. These findings are expected to provide valuable insights for universities, government, and institutions to more effectively prepare students for career challenges and changes. Keywords: Career Adaptability, Career Decision Self-Efficacy, Emotional Intelligence, Peer Support